Design and prototyping of powered sliding door for light commercial vehicles - DEMİR, UĞUR (My University, 2021)
This study presents the powered sliding door (PSLD) design and prototype for light commercial vehicles. First of all, the literature and patent research are done. And the state of the art for sliding door mechanism types and electronic control methods are investigated. Then, the requirements, specifications and regulations of original equipment manufacturers (OEMs) are dealt with and design require-ments and criteria are determined. The performance requirements of the electric motor for the sliding door main unit are calculated according to the design crite-ria and the vehicle door. The main unit is designed to actuate the sliding door as per the design criteria by defining the electric motor. The vehicle door must be unlocked before opening or closing the door. Unlocking actuator is developed for this process. Subsequently, the electronic control unit (DCU) is designed to control the components and actuators. In order to solve the problem frequently encountered in obstacle detection when the vehicle is on a slope, the current lim-its are updated according to the current information read from the electric motor and the vehicle slope information, and the obstacle detection is tried to be per-formed. Finally, testing and verification studies are performed according to the design requirements.
Keywords: Powered sliding door; automotive actuators; obstacle detection; product development process